Hawalah in The Digital Age: The Role of Agents in Facilitating Modern Islamic Financial Transactions - Amrul Muzan; Anna Zahara; Gina Muliana; Muhammad Abdi Zaini (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2025)
This research emphasizes the significance of hawalah in Islamic financial transactions in digital era driven by Islamic fintech. As technological advancements transform financial systems, hawalah remains crucial for facilitating Sharia-compliant international money transfers. This study examines the role of agents in ensuring Sharia compliance in digital hawalah transactions and explores the challenges and opportunities in its implementation. Using a qualitative approach, data were collected from financial agents, users, and regulators, with thematic analysis identifying key patterns. This research concluded that agents play a vital role in maintaining Sharia compliance and enhancing the efficiency of hawalah transactions in digital era. Regulatory challenges and shifts in consumer behavior pose significant hurdles. This study contribute to the formulation of policies and innovations in Islamic financial services. Keywords: hawalah digital; islamic financial agents; sharia compliance; financial transactions; technological innovation Abstrak Penelitian ini mengkaji signifikansi hawalah dalam transaksi keuangan syariah di era digital yang didorong oleh fintech syariah. Ketika kemajuan teknologi mengubah sistem keuangan, hawalah tetap penting dalam memfasilitasi transfer uang internasional yang sesuai dengan syariah. Studi ini menganalisis peran agen dalam memastikan kepatuhan syariah dalam transaksi hawalah digital dan mengeksplorasi tantangan dan peluang dalam penerapannya. Dengan menggunakan pendekatan kualitatif, data dikumpulkan dari agen keuangan, pengguna, dan regulator, dengan analisis tematik yang mengidentifikasi pola-pola utama. Penelitian menyimpulkan bahwa agen memainkan peran penting dalam menjaga kepatuhan syariah dan meningkatkan efisiensi transaksi hawalah di era digital. Namun, tantangan peraturan dan perubahan perilaku konsumen menimbulkan hambatan yang signifikan. Penelitian ini berkontribusi pada perumusan kebijakan dan inovasi dalam layanan keuangan syariah. Kata kunci: hawalah digital; agen keuangan syariah; kepatuhan syariah; transaksi keuangan; inovasi teknologi